THE USE OF PROBLEM BASED LEARNING TO INCREASE STUDENTS’ LEARNING INDEPENDENT AND TO INVESTIGATE STUDENTS’ CONCEPT UNDERSTANDING ON ROTATIONAL DYNAMIC AT STUDENTS OF SMA NEGERI 4 BANDA ACEH - Haji, A. G.; Safriana, S.; Safitri, R. (Jurnal Pendidikan IPA Indonesia, 2015)
The objective of this study is to find out the increase in student’s independent learning and concept understanding on the rotational dynamics after getting the PBL learning and handout. This study was conducted by using "pretest - posttest control group" experimental design. The result of analysis data showed the The average value of N-gain understanding concepts for the experimental group was 74,76%, with the higher category, but for the control group obtained N-gain is 26,76% with low category. N-gain self-regulated laerning for the experimental group was 31% with the medium category and for control group of 20% low category. These results were confirmed by t-test with significant value (0.000) under the probability value (0,05). So that it can be said that PBL learning and the handouts could to improve the student independent learning and concept understanding on the rotational dynamic.